The Role of Harapan Kita Farmers Group in Increasing Prosperity of Farmers in the Suger Lor Village of Maesan Sub-District of - Yulia Agustin; Marjono Marjono; Kayan Swastika (JURNAL HISTORICA, 2019)
Harapan Kita Farmers Group is one of the organizations located in the Suger Lor Village. Formation Harapan Kita Farmers Group because have the same purpose to increase amount of rice production. Because, farmers Suger Lor Village still not produce the maximum harvest. The problems studied are: (1) the background of the establishmen of the Harapan Kita Farmers Group in Suger Lor Village in 1997; (2) the business of the Harapan Kita Farmers Group in increasing the prosperity of farmers in Suger Lor Village in 1997-2018; (3) the effect of the efforts made by te Harapan Kita Farmers Group on the prosperity of farmers in Suger Lor Village in 1997-2018. The research method is the historical method, which consist of heuristis, criticism, interpretation, historiography. The result of the research obtained in this study are: background of the establishment of the Harapan Kita Farmers Group because large are and the condition of farmers still poor. The business of the Harapan Kita Farmers Group do cooperating with the Departement of Agriculture, implement fiver farms, and assist farmers in marketing their crops. The effect of the activities carried out was increasing rice production has an affect on the income farmers in the Suger Lor Village. Keywords: Harapan Kita Farmers Group, Farmers, Prosperity. Harapan Kita Farmers Group is one of the organizations located in the Suger Lor Village. Formation Harapan Kita Farmers Group because have the same purpose to increase amount of rice production. Because, farmers Suger Lor Village still not produce the maximum harvest. The problems studied are: (1) the background of the establishmen of the Harapan Kita Farmers Group in Suger Lor Village in 1997; (2) the business of the Harapan Kita Farmers Group in increasing the prosperity of farmers in Suger Lor Village in 1997-2018; (3) the effect of the efforts made by te Harapan Kita Farmers Group on the prosperity of farmers in Suger Lor Village in 1997-2018. The research method is the historical method, which consist of heuristis, criticism, interpretation, historiography. The result of the research obtained in this study are: background of the establishment of the Harapan Kita Farmers Group because large are and the condition of farmers still poor. The business of the Harapan Kita Farmers Group do cooperating with the Departement of Agriculture, implement fiver farms, and assist farmers in marketing their crops. The effect of the activities carried out was increasing rice production has an affect on the income farmers in the Suger Lor Village. Keywords: Harapan Kita Farmers Group, Farmers, Prosperity.